Making use of logic - Urchs, Max (Logic and Logical Philosophy, 1998)
It seems that Polish logic has always been open to considerations concerning the use of methods and results of formal logic within disciplines. We overview a couple of such Polish contributions to what may be called the realm of applied logic. We take a closer look at the formalization of natural reasoning, inconsistency-tolerant logic, and at the formal analysis of causal nexus.